Wine Consumption in Times of Social Isolation: A Discussion in the Field of Leisure Studies (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2021)
The relationship between leisure and the consumption of alcoholic beverages is something so common and inherent to the human being that practically there are no studies that discuss the topic in its depth. Being, the relationship is linked to conviviality and sociability in moments of parties, celebrations, meetings whether to celebrate some happy or even sad occasion, religious rituals or social improvements. However, it is even more difficult to find that theorization the expressive increase in the consumption of alcoholic beverages related to leisure, in periods of social isolation caused by pandemics, as in the case of the occurrence in 2020 worldwide, caused by the new coronavirus. Thus, the objective of this article is to discuss the statistical data generated by some studies in the first half of 2020 that evidenced the increase in wine consumption in Brazil linking these with leisure studies such as escape from reality, source of pleasure and status. The choice of wine among so many other alcoholic beverages was due to the following reason: while beer consumption, which occurs mainly among friends, fell in the first quarter of 2020, in the same period, wine consumption increased, with purchases in purchases through e-commerce and physical stores, such as supermarkets and wholesalers.